2022
DOI: 10.35568/abdimas.v4i2.1426
|View full text |Cite
|
Sign up to set email alerts
|

Using Digital Marketing to Develop Marketing Strategy for Fish Farmer Group Products in Jehem Village

Abstract: Fish Farmer Group "Mina Kumala Sari" is a fish farming group located in Jehem Village, Tembuku District, Bangli Regency and is engaged in fisheries, especially koi fish. Based on observations, it is known that this group still has problems in marketing the product. By using digital marketing through social media, it is hoped that they can reach the target market of the "Mina Kumala Sari" Fish Farmer Group. The purpose of this community service is to find out the use of digital marketing as a marketing strategy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…Salah satu langkah pertama adalah memiliki situs web atau platform online yang informatif dan menarik, yang mencakup informasi tentang produk ikan, proses budidaya, serta informasi kontak. Selain itu, sosial media seperti Facebook, Instagram, dan LinkedIn dapat digunakan untuk membangun kehadiran online dan berkomunikasi dengan calon pelanggan (Devi, Anggria Wardani, & Adhiya Garini Putri, 2022).…”
Section: Workhop Branding Digitalunclassified
“…Salah satu langkah pertama adalah memiliki situs web atau platform online yang informatif dan menarik, yang mencakup informasi tentang produk ikan, proses budidaya, serta informasi kontak. Selain itu, sosial media seperti Facebook, Instagram, dan LinkedIn dapat digunakan untuk membangun kehadiran online dan berkomunikasi dengan calon pelanggan (Devi, Anggria Wardani, & Adhiya Garini Putri, 2022).…”
Section: Workhop Branding Digitalunclassified
“…Group members have not used online marketplaces such as Shopee and Tokopedia. Previous studies have confirmed that online sales may increase turnover [20], [21]. The marketing training was carried out, starting from mentoring to beautify customized ornamental fish feed packaging, assisting in opening stalls at Shopee and Tokopedia, to Canva application training so that the products displayed in online stalls look attractive.…”
Section: Marketing Trainingmentioning
confidence: 99%
“…Customers are more likely to visit the location of the Fish Farmer Group if the group uses digital marketing, increases promotional content, and posts promotional content as frequently as possible on social media. (Devi, Wardani, & Putri, 2021).…”
Section: Assessing Marketing MIXmentioning
confidence: 99%